Crimes against Nature : Squatters, Poachers, Thieves, and the Hidden History of American Conservation - Jacoby, Karl, 1965- (Book collections on Project MUSE., 2014)
Crimes against Nature reveals the hidden history behind three of the nation's first parklands: the Adirondacks, Yellowstone, and the Grand Canyon. Focusing on conservation's impact on local inhabitants, Karl Jacoby traces the effect of criminalizing such traditional practices as hunting, fishing, foraging, and timber cutting in the newly created parks. Jacoby reassesses the nature of these ""crimes"" and provides a rich portrait of rural people and their relationship with the natural world in the late nineteenth and early twentieth centuries.